2017
DOI: 10.1016/j.nicl.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Specific DTI seeding and diffusivity-analysis improve the quality and prognostic value of TMS-based deterministic DTI of the pyramidal tract

Abstract: ObjectNavigated transcranial magnetic stimulation (nTMS) combined with diffusion tensor imaging (DTI) is used preoperatively in patients with eloquent-located brain lesions and allows analyzing non-invasively the spatial relationship between the tumor and functional areas (e.g. the motor cortex and the corticospinal tract [CST]). In this study, we examined the diffusion parameters FA (fractional anisotropy) and ADC (apparent diffusion coefficient) within the CST in different locations and analyzed their interr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 47 publications
(77 reference statements)
5
68
0
Order By: Relevance
“…We concluded that a distance of 10 mm between tumor border and CST was sufficient to preserve motor function. Comparable results were also cited in some prior studies 33,35,37) . The tumor-CST distance may well be regarded as presumptive predictor of outcome, attributable in part to tumor edema.…”
Section: Improvement In Outcomessupporting
confidence: 88%
“…We concluded that a distance of 10 mm between tumor border and CST was sufficient to preserve motor function. Comparable results were also cited in some prior studies 33,35,37) . The tumor-CST distance may well be regarded as presumptive predictor of outcome, attributable in part to tumor edema.…”
Section: Improvement In Outcomessupporting
confidence: 88%
“…In order to improve the threshold selection, previous standardization attempts suggested a FL threshold of 110 mm and the implementation of a 100%-FAT criterium. The latter described the FA threshold at which only a thin fiber tract was visualized and all other FA values were described in relation to this 100%-FAT value as e.g., 75%-, 50%-or 25%-FAT (Frey et al, 2012;Weiss et al, 2015;Rosenstock et al, 2017;Weiss Lucas et al, 2017). The concept of performing fiber tracking with a FL threshold of 110 mm and a 75%-FAT resulted in a more objective tractography than the previous methods (Frey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The modeled grid was imported into the BrainLab iPlan 3.0 software and fused to the original nTMS data, anatomical T1-weigthed MRI, and DTI dataset. In addition to the cortical ROIs, we created two subcortical ROIs for every subject: the first one (PON-ROI) was placed in the caudal pons based on the color-coded FA map (Rosenstock et al, 2017), while the second (PED-ROI) was located below the cerebellar peduncles to avoid aberrant tracts to the cerebellum. Furthermore, for later comparative analysis, we created an additional cortical ROI from the summation of nTMS points of positive MEPs (i.e., amplitude >50 µV), which were enlarged by 2 mm (nTMS-ROI) in line with the current clinical practice (Krieg et al, 2012).…”
Section: Cortical Roi Selection and Fiber Trackingmentioning
confidence: 99%
“…DTT can identify eloquent tumors in subcortical motor pathways for presurgical planning. [18][19][20] One study reported that changes in diffusion parameters with glioma close to the corticospinal tract are the optimal factor in predicting injury to the corticospinal tract caused by a brain tumor. 18 Another study added that the diffusion parameters are particularly disturbed, and the degree of their impairment correlates with motor deficits.…”
Section: Discussionmentioning
confidence: 99%